35(2X-1)=7(X 4) 3X

35(2X - 1) = 7(X + 4) + 3X

now we solve the brackets, then

70X - 35 = 7X + 28 + 3X

now

70X - 35 = 7X + 3X + 28

70X - 35 = 10X + 28

now subtract 10X on both sides, we get

70X - 10X - 35 = 10X - 10X + 28

60X - 35 = 28

now add 35 on both sides, we get

60X - 35 + 35 = 28 + 35

60X = 63

now divide by 60 on both sides, we get

60X/60 = 63/60

X = 63/60

Hence X = 63/60

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up